Exportación de conserva de papa nabo al mercado de Japón - Castro Remache, Marilyn Joselyn (2022)
The purpose of this project is to develop a Plan for the export of canned turnip potatoes to the Japanese market, which is mainly aimed at supermarkets in the city of Japan. The objective of this research project is to develop the export plan that will serve to promote the commercialization of canned turnip potatoes from the Ordoñez farm, Ecuador has a national demand for vegetables and their derivatives, thanks to the nutrients and benefits it possesses. For this, descriptive research was used to refer to the logistical processes that are carried out and exploratory research to corroborate information provided by Yofre Vicente Ordoñez, head of exports of the Ordoñez farm.......